Strategi Pembelajaran dalam Membangun Kesiapan Mahasiswa Menjawab Tadribat Bahasa Arab di Kelas - Desta Aditya; Muhammad Hasbi i Ashiddieqy; Usamah Abdul Aziz; Angger Bimantara (INDO PUBLISHING, 2026)
This research explores the teaching strategies utilized by lecturers to bolster students' preparedness in tackling Arabic language exercises (tadribat) in the classroom. It also examines students’ readiness for these exercises and identifies challenges faced during their preparation. The study adopted a descriptive qualitative methodology, engaging two lecturers and two second-semester students from STAI Ali Bin Abi Thalib Surabaya, selected through purposive sampling. Data collection methods included observation, in-depth interviews, and documentation, while analysis involved data condensation, data display, and conclusion drawing. Data validity was ensured using source triangulation. The findings indicate that lecturers employed a variety of strategies to enhance learning outcomes. These strategies included fostering commitment through academic contracts, employing random questioning techniques, incorporating scaffolding methods, utilizing visual media and digital tools, and creating an Arabic-speaking environment (bi’ah lughawiyyah). Students demonstrated readiness through self-directed study sessions a day prior to class, the use of digital learning platforms, and engaging in collaborative peer discussions. These approaches collectively enhanced students’ confidence, classroom engagement, and their ability to address exercises with greater precision and speed. Despite these successes, the study also identified notable challenges. These included psychological obstacles, varied educational backgrounds among students, overreliance on AI-based tools, constrained instructional time, and limited opportunities to practice Arabic outside of the classroom setting. The research underscores the critical role of integrating effective teaching strategies, encouraging student autonomy, and fostering supportive learning environments to improve Arabic language proficiency.